Implementasi Teknologi Informasi dan Balance Scorecard Mahasiswa Fakultas Ekonomi dan Ilmu Sosial UIN Suska Riau (Survai Terhadap Mahasiswa Semester VI Prodi Manajemen S1) - Irien Violinda Anggriani (Bahtera Inovasi, 2019)
Progress in the application of information technology ( IT ) made in various areas of the geographical distance was not important to them who had access to it.Anyone connected with IT can access information that is everywhere and communicate with anyone, using the internet. IT encourages fundamental changes in daily life, including in their learning. As one of supporting in a college, implementation information technology the students and teachers visit an industry to learn to PT.Indofood CBP Sukses Makmur,Tbk, Branch of Pekanbaru. to observe, understand and directly know the production process that use information technology. Balance Scoredcard ( BSC ) is management mechanism system to translate the vision and strategy organization into real action field and contributed in the improvement of the quality of graduates and performance college through four, the financial perspective , customers of business process and learning and. internal growth.